Trading off : a grounded theory on how Māori women negotiate drinking alcohol during pregnancy : a thesis presented in partial fulfilment of the requirements for the degree of Master of Public Health at Massey University, Wellington, New Zealand - Stuart, Keriata (Massey University, 2009)
This study aimed to understand how Maori women negotiate decisions about alcohol and pregnancy. It was based in the recognition that Maori women?s decisions about drinking alcohol when pregnant are shaped by social and cultural expectations about gender roles, as well as their knowledge about alcohol and pregnancy. Maori attitudes to alcohol have also been influenced by colonisation and Maori responses to it. Alcohol use in pregnancy also exists in the context of potential impacts, including fetal alcohol spectrum disorder. There is little knowledge about how and why women may or may not drink during pregnancy. The research used grounded theory methods. Information was gathered through in-depth interviews with ten Maori women. The information they provided was analysed using constant comparative analysis, and a series of categories was generated. The grounded theory proposes that Maori women manage decisions about drinking alcohol when pregnant using a process of Trading off. Trading off is supported by three key processes: drawing on resources, rationalising, and taking control of the role. Maori women start by learning the rules about alcohol, get messages about alcohol and pregnancy, change their alcohol use while making role transitions, and use alcohol in the processes of fitting in where you are, releasing the pressure, and carrying on as normal. Trading off is an individual process, but exists in a complex social context. The process is fluid, conditional, and continues throughout pregnancy. The theory must be recognised as my interpretation, although I believe it is grounded in the data, accounts for the data, and offers a new, modifiable and potentially useful interpretation. While the body of theory that can be compared to the theory of Trading off is limited, the interpretation is consistent with several models of health behaviour, including Maori health models. This research has implications for future research, and for the development of programmes to support Maori women.
Keywords: Maori women; Alcohol consumption; Pregnant women; Pregnancy; Fields of Research::320000 Medical and Health Sciences::321200 Public Health and Health Services::321207 Indigenous health